The Determinants and the Size of International Migration in Central and Eastern Europe After 2004 - Organiściak-Krzyszkowska, Anna (Comparative Economic Research. Central and Eastern Europe, 2017)
Migration is a very important socio‑economic issue in the contemporary world. One of the interesting and pertinent research problems worth considering concerns the scale and nature of migration from countries which entered the European Union in 2004 and in the subsequent years. As a result of integration within the European Community, the citizens of member states acquired citizenship within the entire European Union (which is complementary to citizenship in the country of origin). The right of free movement led to the emergence of the migration phenomenon within the territory of the European Union. A well educated and young labour force may be an influential factor in the social and economic development of the European Union members. The enlargement of the EU led to a significant increase in the number of part‑time/temporary migrants. According to statistical data, the number of emigrants from the Central and Eastern European Countries (CEE) to the more prosperous European countries increased from 1,66 million in 2004 to 7,3 million in 2016. Within the context of the scale of economic migration from the CEE, questions should be asked about the determinants and economic consequences of this mobility. The main objective of this article is a diagnosis and evaluation of the determinants and size of migration from the CEE. The analyses are based on Eurostat data. The determinants of migration are presented from the point of view of the push and pull factors theory and related to the situation in the European labour market. An analysis of the size of migration outflow from the CEE countries made it possible to classify them into three groups: countries with a high emigration potential (Latvia, Lithuania, Romania), a moderate emigration potential (Hungary, Bulgaria, Poland, Estonia, Slovakia) and a low emigration potential (the Czech Republic, Slovenia). The economic consequences of migration are shown from the perspective of remittances received from working abroad.